A Yagi-Uda Antenna Implemented with Solar Cells - Ali, Ahmed; Wang, Heesu; Park, Ikmo (2024 IEEE International Workshop on Antenna Technology, iWAT 2024, 2024)
This paper presents a design of a Yagi-Uda antenna implemented with solar cells. An ultra-low-profile copper indium gallium selenide (CIGS)-based solar cell was used as a driver, and a slot was cut in the driver to feed the antenna. A CIGS solar-cell-based reflector and director were added to form a Yagi-Uda antenna. The spacing between the reflector, driver, and director were minimized to increase the solar-cell form factor. A coaxial-to-microstrip line transitiontype feeding structure was used for wideband impedance matching. Three RF decoupler circuits were designed for the driver, reflector, and director so that the antenna and solar cell could function independently. The antenna has overall dimensions of 0.71 λo × 0.61 λo × 0.006 λo at 3.2 GHz, an impedance bandwidth of 56.74%, and a maximum gain of 5.67 dBi within the impedance bandwidth.
Keywords: Cell-be; Cell/B.E; Cell/BE; Gallium selenides; Impedance bandwidths; Integrated antennas; Low-profile; Solar-cell-e integrated antenna; Wideband antenna; Yagi-Uda antennas; solar-cell-e integrated antenna; wideband antenna; Yagi-Uda antenna